Analysis of the Impact of Social and Cultural Functions of Iranian-Islamic Mosques on Tourism Development: A Case Study of Jameh Mosque in Isfahan - Ehsan Ghorbani; Marjan Khanmohamadi (طراحی و برنامه ریزی در معماری و شهرسازی)
In contemporary society, the sacred institution of the mosque has distanced itself from active engagement and social interactions, diminishing its central role in the social fabric. The cultural and religious layers of the mosque have also become less prominent. Considering the importance of tourism development in identifying indigenous culture, beliefs, and promoting religion, this paper aims to explore the potential of tourism development in the case study of Jameh Mosque in Isfahan. The research methodology employed is descriptive-analytical, and the study has practical implications. The necessary data was collected through referencing reputable scientific sources and field observations. The statistical population includes university professors and architectural experts working in academic centers in Isfahan. The questionnaire results were analyzed using one-sample t-tests, Pearson correlation, and SPSS software. Based on the research findings, indicators such as organizing celebrations and public events (score: 4.83), training Islamic architects (score: 4.77), conducting cultural sessions (score: 4.73), and reviving social occasions (score: 4.70) have the greatest impact among the social and cultural performance indicators of Jameh Mosque in Isfahan. The results demonstrate a positive and direct correlation between the thirteen social and cultural performance indicators of Jameh Mosque and tourism development. As these indicators improve in the mosque, tourism will also experience further development. Therefore, focusing on the social and cultural performance indicators of Jameh Mosque facilitates tourism development and enhances local community activities and events within the mosque.